2022
DOI: 10.1111/trf.17170
|View full text |Cite
|
Sign up to set email alerts
|

A large cohort study of the effects of Lewis, ABO, 13 other blood groups, and secretor status on COVID‐19 susceptibility, severity, and long COVID‐19

Abstract: Background Previous studies have reported Blood type O to confer a lower risk of SARS‐CoV‐2 infection, while secretor status and other blood groups have been suspected to have a similar effect as well. Study design and methods To determine whether any other blood groups influence testing positive for SARS‐CoV‐2, COVID‐19 severity, or prolonged COVID‐19, we used a large cohort of 650,156 Danish blood donors with varying available data for secretor status and blood groups ABO, Rh, Colton, Duffy, Diego, Dombrock,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
(146 reference statements)
0
10
0
Order By: Relevance
“…The selective force is presumed to be several pathogens. In fact, non-secretors have been reported to be highly resistant to noroviruses and rotaviruses, and more recently, to COVID-19 infection, albeit weakly [30][31][32]. In addition, recent studies have suggested that secretor status affects susceptibility to a variety of clinical conditions, including some infectious diseases, inflammatory bowel disease, and plasma vitamin B12 levels [33][34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…The selective force is presumed to be several pathogens. In fact, non-secretors have been reported to be highly resistant to noroviruses and rotaviruses, and more recently, to COVID-19 infection, albeit weakly [30][31][32]. In addition, recent studies have suggested that secretor status affects susceptibility to a variety of clinical conditions, including some infectious diseases, inflammatory bowel disease, and plasma vitamin B12 levels [33][34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…A study on the relationship between ABO blood groups and Long COVID infection severity shows that patients with AB blood group have persistent symptoms [ 14 ]. A large cohort study in Denmark, published in 2023, tried to explore the correlation between Long COVID and blood groups but no association was found [ 15 ]. To the best of our knowledge, no research has been carried out on this topic at both local and national levels in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…2 The relationship between COVID-19 contraction and blood group types was still being debated. Although many have used big sample sizes to illustrate the presence of a clear link, 36 several other investigations have shown no connection between COVID-19 infection and blood types. 710 The ABO locus has been linked to genetic connections with both infection risk and disease severity.…”
Section: Introductionmentioning
confidence: 99%